PENGGUNAAN VIDEO TUTORIAL UNTUK MENDUKUNG PEMBELAJARAN AUTOCAD DARING DI MASA PANDEMI VIRUS CORONA - Widya Azhamul Fadhilah Zain; Yuwalitas Gusmareta (Teknik Sipil Universitas Negeri Padang, 2021)
Abstract: A virus called COVID-19 (Coronavirus Diseases-19) is a new type of disease that makes people have to do all activities at home. This requires the learning process in online or online CAD Application courses and makes it difficult for students to understand the learning material. This study aims to support online learning of AutoCAD. R&D or (Research and Development) is the type of research and development that will be used in this research. This development research uses the stages of Ariesto Hadi Sutopo (2003:32). Which consists of 6 stages, namely: concept (concept), design (Design), collecting material (collection of materials), assembly (merging), testing (testing), distribution (distribution). The assessment of learning media uses a questionnaire for material experts, media experts, and students. The results of the assessment of the video tutorial learning media product in the CAD Application course by the material expert 1 obtained an average score of 95% and the assessment by the material expert 2 also obtained an average score of 95% on the indicators of material, explanation, usability, coherence, and motivation. Media experts obtained an average score of 90% on efficient, visual and audio indicators. The assessment of 10 students got an average score of 84% in the